Aprender a ensinar Geografia: a visão de egressos do curso de Pedagogia da UEFS (Univerisdade Estadual de Feira de Santana) - Braga, Maria Cleonice Barbosa (2006)
The present study is at the scope of investigation which search to understand how it s been developed the teaching and learning processes of the specific didactics in Pedagogy Training Course for experienced teachers. More effectively, its is directed to the understanding of teaching and learning at the subject Geography on the Pedagogy First Initial Series of Primary School course, at the Universidade Estadual de Feira de Santana (UEFS). Even though many courses have been implanted in the past few years involving this public, its still rare the researches dedicated to the understanding of its contributions to these teachers practices. These scarcity, together with a particular interest in contribute with the deepness of the question, is the reason for me to do this work, guided for the following question: How do the egresses from the degree in Pedagogia Séries Iniciais do Ensino Fundamental at UEFS, describe and analyze the Geography teaching developed at the course, considering the contributions to the development of their practices inside the classrooms? The theoretical references adopted were: to discuss teaching learning and professional teaching knowledge, we considered the contributions from Maurice Tardif, Marcelo Garcia, Pérez Gómez and, to discuss the different approaches in Geography we adopted the works of William Vesentini, Helena Callai, Lana Cavalcanti, Nídia Pontushcka. In order to do the investigation, we selected seven egresses who were teaching the subject Geography at the first initial series of Primary School since they have finished their degree. The main data collection instrument was the individual interview together with a questionnaire, using a qualitative approach as a research reference in their paths as students of the Basic Teaching and in the course of Pedagogy, in UEFS. It was clear the change in the way of to understand and to teach Geography. The first was the one of the book, of the copy, of the "decoreba"; it was the learned Geography, just, to answer the subjects of the proof. The second was developing of another perspective, characterized essentially by his/her relationship with the concrete life, with the reality of a world that is unequal and unjust. Besides, the data revealed some changes in practice of the current participants of the multiple relationships with the knowledge locked in the degree, besides in the discipline Ensino de Geografia. But they had disclosed also that not learning had of contents specific (concepts, facts, methods of education) and nor of a conception of formation based in the theorypractical relation that they allowed them to develop an education of analysis, critical and reconstruction of the proper teaching exercise.